Isolation, characterization and evaluation of the probiotic potential of a novel Lactobacillus strain isolated from Feta-type cheese. (1st July 2017) - Plessas, Stavros; Nouska, Chrysanthi; Karapetsas, Athanasios; Kazakos, Stavros; Alexopoulos, Athanasios; Mantzourani, Ioanna; Chondrou, Pelagia; Fournomiti, Maria; Galanis, Alex; Bezirtzoglou, Eugenia
Highlights: 45 lactic acid bacteria (LAB) strains were isolated from Feta-type cheese. Strain K5 displayed probiotic potential. Molecular characterization of strain K5 was performed based on multiplex PCR. L. paracasei K5 displays desirable technological properties for probiotic food use. A multiplex PCR assay was developed for the efficient detection of strain K5 in food products. Abstract: In the present study 45 lactic acid bacteria (LAB) strains were isolated from Feta-type cheese and were screened for probiotic potential in a series of established in vitro tests, including resistance to low pH, resistance to pepsin and pancreatin and tolerance to bile salts. The strain K5, which displayed properties similar to or even better than the reference strain Lactobacillus plantarum ATCC 14917, was chosen for further analysis. Firstly, multiplex PCR analysis indicated that the novel strain belongs to the paracasei species. Secondly, the susceptibility against common antibiotics was determined to ensure a safe exploitation of the potentially probiotic strain. Additionally, the performance of L. paracasei K5 as starter in the fermentation of pomegranate juice was studied to evaluate its technological properties. Finally, a novel multiplex PCR assay, based on random amplified polymorphic DNA (RAPD) analysis was developed for its efficient and accurate detection in food products.